EPIDEMIOLOGI KECELAKAAN LALU LINTAS DI JALUR TENGKORAK KABUPATEN WONOSOBO (Studi Kasus: JALAN RAYA PARAKAN KM 10) - Asfi Manzilah; Mateus Sakundarno Adi; Ari Udiyono; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Traffic accidents are unexpected and accidental incidents that involve human and or property casualties. The purpose of this research is to know the effect of traffic accident risk factor in Skull Trails, Kertek Sub-district, Wonosobo District (Case Study: Raya Parakan KM 10 Street). This type of research is observational descriptive with crossectional design. The samples were all vehicles passing the border gate of Wonosobo Regency on Raya Parakan KM 10 Street. Sampling technique using accidental sampling. The results show the highest peak flow during pre-Eid is on Sunday at 15:00 to 17:00 pm with the number of vehicles 5.64%. The proportion of passenger car vehicles is at risk when the highest pre-Eid ul-Fitr is a motorcycle type of 98.90%. The proportion of high risk goods vehicles at pre-Eid ul-Fitr is the type of pickup vehicle of 58.70%. The proportion of the reasons for passenger car vehicles is risky at the highest pre-Idul Fitri time is due to the excess number of people by 58.19%. The proportion of high risk goods vehicles at pre-Eid ul-Fitr is highest due to overload (vehicle height) of 27.42%. The proportion of drivers of public bus vehicle AKAP / AKDP which rested most during pre-Eid al-Fitr at 2.47%. It is necessary to increase the operation of yellow janur and public buses to anticipate motorcycles and overloaded pickups. There needs to be a health cadre in the terminal to help check the physical condition of AKAP/AKDP bus drivers, as well as coordinate working hours and reserve drivers.